2015
DOI: 10.3171/2014.10.spine13805
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of screw constructs for atlantoaxial fixation in cadavers: a systematic review and meta-analysis

Abstract: OBJECT The unique and complex biomechanics of the atlantoaxial junction make the treatment of C1–2 instability a challenge. Several screw-based constructs have been developed for atlantoaxial fixation. The biomechanical properties of these constructs have been assessed in numerous cadaver studies. The purpose of this study was to systematically review the literature on the biomechanical stability achieved using various C1–2 screw constructs and to perform a meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 45 publications
2
74
0
6
Order By: Relevance
“…29 In a cadaveric study, Du et al analyzed the biomechanical difference between C-2 pars screws and C-2 pedicle screws after C1-2 arthrodesis and concluded that the C-2 pedicle screws have twice the pullout strength of the C-2 pars screws. 6 In the case of reliable spinal navigation, the C-2 short screws may be reserved for cases in which anatomical landmarks do not allow the placement of C-2 pedicle screws. An important aspect for posterior C1-2 fixation using C-1 lateral mass screws and C-2 pedicle screws is the bicortical placement of screws.…”
Section: Discussionmentioning
confidence: 99%
“…29 In a cadaveric study, Du et al analyzed the biomechanical difference between C-2 pars screws and C-2 pedicle screws after C1-2 arthrodesis and concluded that the C-2 pedicle screws have twice the pullout strength of the C-2 pars screws. 6 In the case of reliable spinal navigation, the C-2 short screws may be reserved for cases in which anatomical landmarks do not allow the placement of C-2 pedicle screws. An important aspect for posterior C1-2 fixation using C-1 lateral mass screws and C-2 pedicle screws is the bicortical placement of screws.…”
Section: Discussionmentioning
confidence: 99%
“…The atlantoaxial pedicle screw, pioneered by Goel et al [11] and modified by Harms et al [12], was one of the most commonly applied techniques. Moreover, the biomechanical stability of atlantoaxial pedicle screw is significantly higher than that of the wiring technique [7, 8], as well as that of the transarticular screw technique [2, 13]. In terms of the bone fusion rates, there is no distinction between the atlantoaxial pedicle screw and the transarticular screw technique [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Without intervertebral disc between the atlas and the axis, the stability of atlantoaxial complex relies solely on the atlantoaxial joint and the transverse ligament [2, 3]. Any injury of structure above may cause atlantoaxial instability [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many disorders such as trauma, tumors, rheumatoid arthritis, congenital, inflammatory, and infectious diseases can cause instability of the first two vertebrae (9). Recently, fixation techniques have provided more stability and safety in surgery (8).…”
Section: █ Discussionmentioning
confidence: 99%